Zimbabwe : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes economic developments in Zimbabwe during the 1990s. The paper highlights that the path of the economy since 1990 has been dominated by the impact of the severe drought in 1992. Value added in the agricultural sector declined by 24 percent in 1992, but the impact of the drought reached much further into the economy. The recovery from the drought was led by a sharp rebound in agricultural production in 1993, which grew by 48.5 percent, boosted by an above-average harvest for maize and a recovery in tobacco production.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet